A giant urinary bladder stone in the mummy of Lebanese Maronite Patriarch Joseph Tyan (1760–1820) and its environmental and nutritional implications. Issue 1 (February 2017) - Capasso, L.; Licata, M.; Pinto, A.; Fernianos, F.; Azizi, T.; Manzoli, L.; Centrella, D.; D'anastasio, R.
Abstract: Introduction: Historical sources and anthropological investigations, with the indispensable support of radiology, bring to light pathological evidence of the past. Case presentation: The purpose of this article is to present the radiological investigation conducted on the mummy of the Maronite Joseph Tyan (1760–1820), a famous patriarch who guided the Lebanese Maronite community during a critical period of its history. The natural mummy of the Patriarch was temporarily removed from its burial site to certify the degree of preservation. Conventional radiography was necessary to determine the state of the internal organs and any physical abnormalities, and to clarify the degree of conservation of the mummy. Discussion: Radiological analysis uncovered an exceptional case of a large urinary bladder stone. This pathological evidence confirms historical documentary sources that in the last years of his life the Patriarch suffered from abdominal pain and urinary problems. We can suppose that the environment and diet of the Maronite community, limited by restricted agricultural resources, was the possible cause of the urinary bladder stone, as today the epidemiology of these diseases demonstrates links with mainly cereal diets in rural areas. Highlights: Paleoradiological analysis: a radiological approach to study mummies. The anthropological and radiological analysis of the Mummy of Patriarch Joseph Tyan Urinary bladder stone: radiological investigations. Paleopathological literature of urinary bladder stone.